Lothario's Corpse : Libertine Drama and the Long-Running Restoration, 1700-1832 - Gustafson, Daniel; Gustafson, Daniel (Book collections on Project MUSE., 2020)
"Lothario's Corpse unearths a performance history, on and off the stage, of Restoration libertine drama in Britain's eighteenth and early nineteenth centuries. While standard theater histories emphasize libertine drama's gradual disappearance from the nation's acting repertory following the dispersal of Stuart rule in 1688, Daniel Gustafson traces its persistent appeal for writers and performers wrestling with the powers of the emergent liberal subject and the tensions of that subject with sovereign absolutism. With its radical, absolutist characters and its scenarios of aristocratic license, Restoration libertine drama became a critical force with which to engage in debates about the liberty-loving British subject's relation to key forms of liberal power and about the troubling allure of lawless sovereign power that lingers at the heart of the liberal imagination. Weaving together readings of a set of literary texts, theater anecdotes, political writings, and performances, Gustafson illustrates how the corpse of the Restoration stage libertine is revived in the period's debates about liberty, sovereign desire, and the subject's relation to modern forms of social control. Ultimately, Lothario's Corpse suggests the 'long-running' nature of Restoration theatrical culture, its revived and revised performances vital to what makes post-1688 Britain modern."